Efektivitas Media Poster Intervensi Diet Anak Autis Terhadap Peningkatan Pengetahuan Ibu di SLBN Pembina Kupang - Nanci Kaka; Afrona E. L. Takaeb; Rut R. Riwu (Journal of Health and Behavioral Science, 2020)
Autistic is a very complex developmental disorder in children, which begins to appear before the age of three years. Autistic children have certain food diet so that a mother must have good knowledge about the right foods choices for the children. The increasing of knowledge can be done by various ways, one of them is using poster media. The purpose of this study was to determine the effectiveness of using diet intervention poster media for autistic children to increase the knowledge of mothers in SBLN Pembina Kupang in 2019 year. This study uses One Group Pretest Postest Design and descriptive analysis method. The population are all mothers who have autistic children especialy 16 mothers as a sample. The results shows that using poster media is effective in order to increase mothers knowledge about diet intervention of autistic children (This can be seen from the mean value of the pretest that is 64.38 to 83.75 (it shows that there is an increasing amount 19.37 from early knowledge).